Newly released high yielding single cross maize hybrids for different ecologies of India - Sciences, Agricultural (The Indian Journal of Agricultural Sciences, 2019)
The genetic enhancement through breeding for high yielding single cross hybrids paid rich dividend for enhancing productivity of maize in the world and same holds true with India. Central Sub Committee on Crop Standards, Notification and Release of Varieties for Agricultural Crops (CSC on CSN & RVAC) notified six new maize hybrids during 2017-18 in field corn (03), baby corn (02) and popcorn (01) developed by Indian Council of Agricultural Research (ICAR), Indian Institute of inaize Research (IIMR), Ludhiana. These hymnals have been recommended for cultivation in various agro ecologies of the country. These (newly release) hybrids are having, high grain yield, multiple disease tolerance, nutrients responsiveness, and attractive grain colour in normal maize and popcorn, while have all desirable characteristics of popcorn (high grain yield, popping percentage) and baby corn.